Determination of transfer functions of the automatic electrohydraulic drive for special process equipment - Таванюк, Татьяна Яковлевна (Technology audit and production reserves, 2015)
This article discusses the improvement of special technological equipment due to the development of mathematical models of work processes that occur in the equipment and take into account the particular purpose of the process equipment. The main objective is to construct a mathematical model and obtaining the transfer functions of the electro-hydraulic drive equipment with passport data of standard devices and drive devices. The linearization of the mathematical model is made on the basis of the analysis of dynamic and statistical characteristics of work processes in equipment subject to a number of assumptions. The developed mathematical model and transfer function of the system allows you to perform a stability analysis, assessment of the quality of regulation and correction of dynamic characteristics based on passport data elements of the drive. The research results can be used by engineers involved in the development of automatic control systems of special technological equipment. A mathematical model is proposed in the work enables the development of automatic control system, which will expand the functionality and efficiency of special technological equipment.